Competences of municipalities in waste economy - Eva Mihaliková; Katarína Čulková; Marcela Taušová; Tomáš Pavlik (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2018)
Healthy living environment is basic factor of modern society, orientated to the sustainable development. Waste economy presents activity, orientated to the avoiding and limitation of waste rising and decreasing of their negative impacts to the living environment. Slovak Republic gives to the tasks of living environment intensive attention from the view of legislative and economic measurements. Every year financial means are invested to the protection of living environment and there is created database and system for monitoring of living environment situation. Contribution is orientated to the competence of municipalities in area of waste economy. The goal is to analyze volume of fees from communal waste that present part of tax incomes for municipalities and to show its development in relation to produced volume of waste. During elaboration of the contribution we resulted first of all from the content law of waste and local taxes and fee for communal waste. Results show presently increasing of environmental awareness of public, resulting in decreasing production of mixed communal waste and increasing separated waste. Such situation could contribute to the support of circular system of economy in the country